TANTANGAN PENDIDIKAN ISLAM DAN BUDAYA LOKAL PADA ERA GLOBALISASI DI INDONESIA - Akhmad Syarief Kurniawan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2017)
One of the major problems faced by Indonesia (and other nations) is related to the process (transformation) from an agrarian society to an industrial society and information, which is characterized by a variety of physical changes, social institutions as well as a shift in the value system. These changes are accompanied also a clash between traditional values ​​inherent in the agrarian culture with cultural values ​​and culture industry information. Education is essentially an attempt to pass a value, which will be a helper and guide mankind in life, and also to improve the fate of human civilization. Globalization delivered by modernization and globalization and rooted in Western culture has indeed been giving a lot of achievements for the nations in various fields of life. Education, agriculture, medicine, communications, entertainment and physical infrastructure greatly benefited by the presence of modernization and globalization.